2017
DOI: 10.3324/haematol.2016.158808
|View full text |Cite
|
Sign up to set email alerts
|

A risk factor analysis of outcomes after unrelated cord blood transplantation for children with Wiskott-Aldrich syndrome

Abstract: Wiskott-Aldrich syndrome is a severe X-linked recessive immune deficiency disorder. A scoring system of Wiskott-Aldrich syndrome severity (0.5–5) distinguishes two phenotypes: X-linked thrombocytopenia and classic Wiskott-Aldrich syndrome. Hematopoietic cell transplantation is curative for Wiskott-Aldrich syndrome; however, the use of unrelated umbilical cord blood transplantation has seldom been described. We analyzed umbilical cord blood transplantation outcomes for 90 patients. The median age at umbilical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 35 publications
3
19
0
1
Order By: Relevance
“…Clinical efficacy and safety were confirmed by several large phase III trials, including the MabEASE, SABRINA and SAWYER studies, which demonstrated no difference in clinical outcomes between intravenous and subcutaneous routes of rituximab administration. [65][66][67] Safety findings appeared comparable as well, and no unexpected safety signals have been generated. However, the subcutaneous formulation has been associated with a slightly increased risk of administration reactions in some trials, as well as local injection site reactions, but these seem to be generally mild and easily managed.…”
Section: Rituximabmentioning
confidence: 64%
See 1 more Smart Citation
“…Clinical efficacy and safety were confirmed by several large phase III trials, including the MabEASE, SABRINA and SAWYER studies, which demonstrated no difference in clinical outcomes between intravenous and subcutaneous routes of rituximab administration. [65][66][67] Safety findings appeared comparable as well, and no unexpected safety signals have been generated. However, the subcutaneous formulation has been associated with a slightly increased risk of administration reactions in some trials, as well as local injection site reactions, but these seem to be generally mild and easily managed.…”
Section: Rituximabmentioning
confidence: 64%
“…Estimated 3-yr PFS was 90% in the obinutuzumab plus bendamustine group and 84% in the obinutuzumab plus CHOP group. 126 The GADOLIN trial was the first randomized phase III study to demonstrate the efficacy of an alternative anti-CD20 monoclonal antibody in rituximab refractory indolent NHL. Obinutuzumab plus bendamustine (G-B) followed by obinutuzumab maintenance was compared to single-agent bendamustine induction in patients who had been either refractory to a rituximab-containing regimen or had experienced progression during or within 6 months of receiving rituximab.…”
Section: Indolent Hematological Malignanciesmentioning
confidence: 99%
“…The first Brazilian HSCT was performed in 1979 at the Federal University of Parana, but only in 1990 was the first patient with PID (Chediak-Higashi Syndrome) transplanted at the National Cancer Institute in Rio de Janeiro. From personal communications at the beginning to the participation of international committees and studies (EBMT, PIDTC, CIBMTR), as well as networking with experienced transplant physicians, this collaboration has enabled significant progress in the field, both in numbers and quality of care [10,[21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The cumulative incidence of neutrophil recovery at day 60 was 89% and that of grade II–IV aGVHD at day 100 was 38%. The use of methotrexate for GVHD prophylaxis delayed engraftment ( P = 0.02), but decreased aGVHD ( P = 0.03) . As expected, children transplanted from UCB experienced relatively delayed engraftment.…”
Section: Discussionmentioning
confidence: 99%